Effectiveness of health belief model-based reproductive health education on menarche preparedness: A systematic review - Nurhaisa, Sitti; Wahyuni, Sri; Susanto, Herry (School of Health Sciences Al-Ma'arif, 2026)
Background: Menarche preparedness is an important component of adolescent reproductive health because inadequate knowledge, negative perceptions, and anxiety may hinder girls’ ability to adapt to their first menstruation. Health education based on the Health Belief Model (HBM) has been increasingly used to improve adolescent readiness by addressing beliefs, perceptions, and preventive behaviors related to reproductive health. Objective: This systematic review aimed to evaluate the effectiveness of HBM-based reproductive health education on menarche preparedness among adolescent girls. Methods: Literature searches were conducted in ProQuest, Scopus, ScienceDirect, and SAGE Journals, with additional searching through grey literature and reference lists. The search covered publications from 2015 to 2025 in English and Indonesian. Eligible studies included quantitative intervention studies examining HBM-based reproductive health education in relation to menarche preparedness or closely related outcomes among adolescent girls. Data were extracted using a structured form and synthesized narratively because of heterogeneity in study design, intervention format, and outcome measures. Results: A total of 30,651 records were identified, of which 42 studies met the eligibility criteria for inclusion. The reviewed evidence consistently showed that HBM-based reproductive health education improved menstrual knowledge, increased positive attitudes, reduced anxiety, and enhanced emotional and behavioral readiness for menarche. Several studies also demonstrated improved menstrual hygiene practices and stronger preparedness when family support and culturally sensitive approaches were incorporated. Although the included studies varied in design and measurement, the overall direction of evidence indicated a beneficial effect of HBM-based educational interventions on adolescent girls’ preparedness for menarche. Conclusion: HBM-based reproductive health education is effective in improving adolescent girls’ preparedness for menarche across cognitive, emotional, and behavioral domains. The integration of theory-based, culturally appropriate, and family-supported educational strategies into school and community health programs may strengthen adolescent reproductive health outcomes.